Inconstitucionalidad de los jueces de coactiva con respecto a al jurisdicción y competencia. - Mejía Coello, Jorge Luis (2014)
Therefore, known Coercive Judges are employees or public officials who do not belong to the judiciary, but are part of the executive branch, so constitutionally and legally can not perform the functions of administration of ordinary justice.